Factors influencing training effectiveness at Petronas LNG LTD., Petronas Twin Towers, Kuala Lumpur / Sarah Liyana Mohd Johari - Mohd Johari, Sarah Liyana (Faculty of Business and Management, 2020)
The purpose of this study is to investigate the factors influencing training effectiveness by examining the trainee’s characteristic, training design and work environment. To asses these factors towards training effectiveness, a quantitative approach using surveys from employees in PETRONAS LNG Ltd at PETRONAS Twin Tower was conducted. This study managed to obtain an 87.3% response rate. A total of data from 262 respondents represented by various departments had been analysed. The data collected were analysed by using Statistical Package for the Social Science (SPSS) Version 23 Software. The sampling used was convenience sampling. The research findings show that trainee’s characteristic, training design and work environment has a significant relationship with training effectiveness. This study provides valuable insight on the organizational, individual and training related characteristic on the factors that influence training effectiveness in an Oil & Gas company. Therefore, it was recommended that carefully thought out training incentives and planning should be provided to all employees to enable them to enhance their skills and upgrade their knowledge from the training completed. Employees should also prepare their mindset to attend training as it has shown to have an influence on training. Finally, foreseeable future research can be conducted to cover other variables like perceived organizational support, organizational commitment, job embeddedness and type of training which might affect training effectiveness.